Regional Approaches to Enforcing MARPOL: Lessons from the European Union and ASEAN - Sade, Juswan (Collaborate Engineering Daily Book Series, 2024)
This paper provides a comparative analysis of the enforcement of the International Convention for the Prevention of Pollution from Ships (MARPOL) within two regional frameworks: the European Union (EU) and the Association of Southeast Asian Nations (ASEAN). Using a mixed-method approach, the study examines key factors such as regulatory coherence, institutional capacity, compliance monitoring, and economic challenges that affect MARPOL enforcement in these regions. The results reveal that the EU's enforcement is more advanced due to its harmonized legal frameworks, centralized oversight through the European Maritime Safety Agency (EMSA), and robust technical capacity. In contrast, ASEAN faces fragmented enforcement, limited institutional capacity, and economic constraints, leading to varying levels of compliance across member states. The study identifies best practices from the EU that could inform improvements in ASEAN’s enforcement mechanisms, emphasizing the need for enhanced regional cooperation and capacity building. These findings offer valuable insights for global efforts to strengthen MARPOL enforcement, particularly in developing regions with similar challenges.